The impact of smartphone addiction on creativity among college students: a moderated mediation model of negative emotion and perceived social support - Guo, Ju; Song, Xueqian; Li, Guiqing; Wen, Ge (Frontiers in Psychiatry, 2025)
IntroductionSmartphone addiction has a negative impact on creativity among college students, which has attracted extensive attention from scholars.MethodsIn this study,we surveyed 2900 Chinese college students using the Smartphone Addiction Scale, Negative Emotion Scale, Perceived Social Support Scale, and Creativity Self-evaluation Scale to explore the impact mechanism of smartphone addiction on creativity.ResultsResults from the hierarchical regression analysis indicated that smartphone addiction has negative influence on creativity in college students (b=-0.158, P<0.001), but positive impacts on negative emotion (b=0.568, P<0.001). The bootstrap analysis indicated that perceived social support not only negatively modulates the impact of negative emotion on creativity, but also modulates the mediating effect of negative emotion on the relationship between smartphone addiction and creativity among college students.DiscussionThese conclusions extend the current research on the hazards of smartphone addiction. According to the results of this study, this article provided practical recommendations for teachers and college students in China.